Implementation of the Fisher Yates Shuffle Algorithm in Medical Equipment Learning Applications with Augmented Reality Technology - Novi Airmawani; Ari Usman; Sarudin Sarudin (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2022)
At this time there are more and more types of medical devices which include goods, instruments or other tools including each component, part or equipment produced. Basically, many people have not been able or are still minimal in knowing medical equipment. One way to provide knowledge to the community is through socialization. Socialization equipped with media that is in accordance with technological developments will facilitate and greatly help the community, namely smartphone media using Augmented Reality technology using the Marker Based Tracking method. This research will build an application for the introduction of medical devices that will combine Augmented Reality technology and the Marker Based Tracking method with the Fisher Yates Shuffle algorithm. The purpose of this research is to produce an application for the introduction of medical devices based on Android and apply the Marker Based Tracking method in Augmented Reality technology with the Fisher Yates Shuffle algorithm in making random questions. The results of this study are in the form of applications that apply augmented reality technology and the Fisher Yates Suffle algorithm in introducing medical devices.